2011
DOI: 10.1074/jbc.m111.234047
|View full text |Cite
|
Sign up to set email alerts
|

Abundant Non-canonical dUTP Found in Primary Human Macrophages Drives Its Frequent Incorporation by HIV-1 Reverse Transcriptase

Abstract: Terminally differentiated/non-dividing macrophages contain extremely low cellular dNTP concentrations (20 -40 nM), compared with activated CD4 ؉ T cells (2-5 M). However, our LC-MS/MS study revealed that the non-canonical dUTP concentration (2.9 M) is ϳ60 times higher than TTP in macrophages, whereas the concentrations of dUTP and TTP in dividing human primary lymphocytes are very similar. Specifically, we evaluated the contribution of HIV-1 reverse transcriptase to proviral DNA uracilation under the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 53 publications
4
43
0
Order By: Relevance
“…An enigmatic feature of SAMHD1 activity in resting immune cells is the presence of elevated dUTP levels in an otherwise depleted dNTP pool background (26,27). Given our findings that dUTP is an excellent substrate, there must be undiscovered regulatory mechanisms that allow dUTP levels to persist or accumulate after the other dNTPs have been depleted.…”
Section: Discussionmentioning
confidence: 97%
“…An enigmatic feature of SAMHD1 activity in resting immune cells is the presence of elevated dUTP levels in an otherwise depleted dNTP pool background (26,27). Given our findings that dUTP is an excellent substrate, there must be undiscovered regulatory mechanisms that allow dUTP levels to persist or accumulate after the other dNTPs have been depleted.…”
Section: Discussionmentioning
confidence: 97%
“…This is due to the higher discrepancy between dNTP and rNTP levels in macrophages (4). Also, previously published studies have shown that the presence of rNMPs in a DNA template causes DNA polymerases to pause during DNA synthesis (7,23). Thus, we tested whether the presence of rNMPs in DNA templates also has the same pausing impact on HIV-1 RT-mediated DNA synthesis.…”
Section: An Rnmp Embedded Within a Dna Template Induces Pausing Of Himentioning
confidence: 99%
“…Finally, if the viral cDNA is uracilated to a sufficiently high density (12,25), it seems inevitable that the host nuclear UNG would excise the uracils, leading to its degradation once it entered the nucleus. There is little or no experimental data available to establish the importance of any of the above possible outcomes in human cells.…”
Section: Significancementioning
confidence: 99%
“…Not surprisingly, dUTPase and UNG are coordinately regulated throughout the cell cycle of dividing cells, with the highest expression levels during the G1 and S phases (9,10). However, in quiescent cells such as macrophages and neurons, dUTP can accumulate to high levels, and mRNA expression of both enzymes is barely detectable (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation